Effect of tool geometrical parameters on friction stir welding joint properties of aluminum alloy AA6061 - Srinivasa Rao, P. (Asian Research Publishing Network, 2016)
Friction stir welding (FSW) process is a solid state joining process in which a non-consumable tool is used to generate frictional heat in the abutting surfaces. The welding parameter such as welding speed, tool rotational speed, and tool profile plays a major role in deciding the weld joint strength. In this investigation, effect of welding parameters and tool pin profile on Mechanical properties in AA6061 aluminum alloy was studied. Friction stir welding of aluminum alloy plates with a thickness of 6 mm are used to perform Friction Stir Weld joints. Tapered cylindrical, and square pin profiles have been used to fabricate the joints at three different rotational speeds i.e. 1500, 2000 and 2500 rpm with two traverse speeds of 20 and 40 mm/min. The mechanical properties (tensile strength, hardness) of the joints have been evaluated and analyzed. It has been observed that the design of tool pin profile has considerable effect on tensile properties. Square pin profile tool produces the best tensile properties compared to tapered cylindrical tool pin profiles. Â© 2006-2016 Asian Research Publishing Network (ARPN).